Etnoparenting: Madurase Ethnic Women’s Parenting Viewed from the Perspective of Social Status - Fitroh, Siti Fadjryana; Oktavianingsih, Eka; Putri, Rizka Mutiara; Eka M, Ameilia (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Views regarding social status have a big influence on individuals in determining their social life, this influences people's perceptions of how they act, especially Madurese people. There are many classifications of social status, but it is focused on the social status of honor (Neng/Nyai), knowledge (Teacher) and heredity (Housewife). These differences will have an impact on the individual's smallest social life, namely the family. This research was conducted involving Madurese ethnic female subjects who had early childhood. The aim of this research is to analyze the parenting patterns of Madurese ethnic women in terms of social status. This research model is included in the qualitative research category with a focused interview approach. Data sources, namely interviews and documentation. The analysis process, namely: 1) data reduction; 2) data presentation; and 3) drawing conclusions. The results of the research state that the upbringing of Madurese ethnic women is viewed from the perspective of social status. The results in the context of the element of faith, the similarities between the three groups apply parental responsiveness in the aspect of warm communication and parental demandingness in the aspect of intrusiveness, strictness and arbitrary exercise of power. In the context of providing education, the honor group applies parental responsiveness in warm communication, the science group applies parental demandingness in the aspects of restrictiveness, demandingness and strictness, the hereditary group applies parental demandingness in the aspect of intrusiveness.